2016
DOI: 10.1002/lary.25904
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly myringoplasty for total, subtotal, and annular perforations

Abstract: 4. Laryngoscope, 126:2565-2568, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
46
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 13 publications
4
46
2
Order By: Relevance
“…Butterfly cartilage tympanoplasty is a technique with high success rates. Several other studies have also reported similar rates [ 1 , 7 - 10 ]. Bhattacharya et al [ 9 ] reported 93.3% success rate, whereas Mauri et al [ 10 ] reported 88.2% success rate.…”
Section: Discussionsupporting
confidence: 69%
“…Butterfly cartilage tympanoplasty is a technique with high success rates. Several other studies have also reported similar rates [ 1 , 7 - 10 ]. Bhattacharya et al [ 9 ] reported 93.3% success rate, whereas Mauri et al [ 10 ] reported 88.2% success rate.…”
Section: Discussionsupporting
confidence: 69%
“…While originally advocated for small to medium-sized central perforations, indications for the inlay technique have expanded to include marginal and subtotal perforations. 11 Higher failure rates in these situations led Eavey et al to modify their technique to include custom contouring and the addition of a split thickness skin graft lateral to the cartilage-perichondrial graft. 12 The recent addition of endoscopic visualization has expanded the potential patient population to include children under the age of 5 years and those with prominent anterior canal bulges, who were not candidates for transcanal microscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…TFE is technically difficult to integrally detach the tympanomeatal flap and form the tunnel because of the bleeding skin of the external auditory canal (EAC) and one-handed operation in endoscopic technique. Although butterfly cartilage myringoplasty does not require TFE for most TM Perforations, medial canal wall skin should be elevated to expose the bony annulus for large marginal perforations [15,16]. This study explored endoscopic cartilage myringoplasty with the removal of a small rim of the EAC to repair marginal perforations.…”
Section: Introductionmentioning
confidence: 99%